2006
DOI: 10.1111/j.1442-2042.2006.01543.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the duration of ureteral stenting following endopyelotomy: Animal study

Abstract: Ureteral stent placement for 1 week is insufficient in order to assure correct healing and evolution of the UPJ following endopyelotomy. Stenting for 3 weeks is effective, and it is not necessary to extend stenting time to 6 weeks. Endoluminal ultrasound is of great use in determining the effects of endourological techniques in the ureter and the retroperitoneal space. It is also useful for deciding which therapeutic technique to use, and for inserting the Acucise in order to prevent iatrogenic problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…our institutional ethics committee approved the experimental protocol. Hydronephrosis of the beagles was induced by ligating the right ureter partially to the psoas . After 2–4 weeks, hydronephrosis grade was evaluated using a sonographic scanner (IU22; Phillips, Amsterdam, Netherlands) and a 2D US probe (C5‐2).…”
Section: Methodsmentioning
confidence: 99%
“…our institutional ethics committee approved the experimental protocol. Hydronephrosis of the beagles was induced by ligating the right ureter partially to the psoas . After 2–4 weeks, hydronephrosis grade was evaluated using a sonographic scanner (IU22; Phillips, Amsterdam, Netherlands) and a 2D US probe (C5‐2).…”
Section: Methodsmentioning
confidence: 99%
“…The importance of using a stent postoperatively to act as a scaffold for urothelial myofibroblast regeneration and to prevent urinoma formation is undisputed [8] . However, the optimal stent size for promoting satisfactory UPJ healing has not been determined yet [9] .…”
Section: Discussionmentioning
confidence: 99%
“…A healing score was developed which included urothelial resurfacing, mural inflammation, lamina propia fibrosis, muscular layer fibrosis, musculature integrity and serosal alterations. The alterations were assessed separately for each parameter [7,8] . To this end, each parameter was graded according to the following range of scores: 0 = no histopathologic changes; to 3 = worst effect in histopathologic architecture.…”
Section: Phase Imentioning
confidence: 99%
See 1 more Smart Citation
“…Stenting duration to treat perforations is usually 4-6 weeks [9] . However, it has been experimentally observed that 3-weeks provide the same results regarding ureteral healing, which is an advantage, as reducing stenting duration decreases the adverse effects associated with double-J stents [45] . When lesions are diagnosed late, the placement of a double-J stent for 8-12 weeks is the first therapeutic option [34] .…”
Section: Treatment Of Perforations and Their Complicationsmentioning
confidence: 99%